Resposta :
Olá, bom dia ☺
Resolução:
[tex]\boxed{\dfrac{1}{x} - \dfrac{1}{x+1} = \dfrac{1}{6}}[/tex]
m.m.c(x,x+1,6)=6x(x+1)
[tex]\dfrac{6(x+1)}{6(x+1)} - \dfrac{6x}{6x(x+1)} = \dfrac{x(x+1)}{6x(x+1)}[/tex]
Eliminando os denominadores...
[tex]6(x+1) - 6x = x(x+1) \\ \\ 6x + 6 -6x = x^2 +x \\ \\ x^2 +x - 6 = 0[/tex]
Valor de delta:
[tex]\Delta = b^2 -4ac \\ \\ \Delta=(1)-4.(1).(-6) \\ \\ \Delta=25[/tex]
Valores de x:
[tex]x=\dfrac{-b\pm\sqrt{\Delta} }{2a} \\ \\ x=\dfrac{-1\pm5 }{2} \\ \\ x_{1}} = \dfrac{-1+5}{2} = 2 \\ \\ x_{2} = \dfrac{-1-5}{2} = -3[/tex]
Soma das raízes:
[tex]x_{1} + x_{2} \\ \\ 2-3 \\ \\ = -1[/tex]
Resposta: Letra E
Bons estudos :)